Vascular Response after Directional Coronary Atherectomy for Left Main Bifurcation Lesion. (14th December 2021) - Kobayashi, Norihiro; Yamawaki, Masahiro; Hiraishi, Mana; Mori, Shinsuke; Tsutsumi, Masakazu; Honda, Yohsuke; Chishiki, Toshiki; Makino, Kenji; Shirai, Shigemitsu; Mizusawa, Masafumi; Yamaguchi, Kohei; Nakano, Takahide; et al.
Abstract : Aims . To evaluate the vascular response after directional coronary atherectomy (DCA) for left main (LM) bifurcation lesion. Methods . This study was a retrospective, single-center study enrolling 31 patients who underwent stentless therapy using DCA followed by drug-coated balloon (DCB) angioplasty for LM bifurcation lesion. We compared intravascular ultrasound (IVUS) findings before and after DCA. Results . After DCA, the lumen and vessel areas significantly increased, whereas the plaque area (PA) and %PA were significantly reduced. When the lesions were divided into small vessel and large vessel groups using the median value of the vessel area, the maximum balloon pressure of the DCA catheter was greater in the large vessel group. Changes in the lumen and vessel areas were also significantly greater in the large vessel group. On the other hand, the changes in PA and %PA were similar between groups. Conclusions . The main vascular responses associated with lumen enlargement after DCA were plaque reduction and vessel expansion. Contribution of vessel expansion to lumen enlargement was larger than the effect of plaque reduction in large vessel lesions.